#1**+10 **

Best Answer

n = 51

$${\left(-{\mathtt{1}}\right)}^{{\mathtt{51}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}{\mathtt{\,\times\,}}{\mathtt{51}} = {\mathtt{50}}$$

.

Alan
May 26, 2015

#3**+5 **

Notice that this wouldn't be too difficult to solve........the first term is either -1 or 1.....

Let's suppose it was 1.....then "n" would have to be even........rearranging the equation, we have

n = 50 - 1 = 49.......but this is a contradiction, because n is even

If n were odd, we would have {again, rearranging}

n = 50 + 1........and this* must* be the solution, because

(-1)^51 + 51 = 50 → -1 + 51 = 50 ..... which is true.....!!!

CPhill
May 26, 2015